The optimization of electrochemical hydride generation technology for treating antimony-containing wastewater - Jingjing Chen; Guoping Zhang; Yi Bai; Yan Xiong; Xing Liu (PLoS ONE, 2025)
Antimony (Sb) is extensively utilized in industrial activities, but most of its compounds exhibit human toxicity and are classified as priority-controlled pollutants. Unlike traditional electrochemical methods that remove metallic pollutants via coagulation or precipitation, electrochemical hydride generation technology converts antimony (Sb) in wastewater into stibine gas (SbH3) for efficient removal. Furthermore, the generated SbH₃ can be decomposed thermally to partially recover metallic antimony. In synthetic wastewater treatment (Sb = 5 mg/L), the proton exchange membrane (Nafion117) electrolysis device achieved an antimony removal efficiency of 72.8 ± 2.2%, outperforming traditional cation-exchange membranes. This enhancement is attributed to the membrane’s proton-selective transport and high H conductivity. Increasing the temperature enhanced the generation and release of SbH3, with the higher removal efficiency of 87.3 ± 2.6% achieved at approximately 30 °C. However, temperatures exceeding 30 °C could lead to the partial decomposition of SbH3 back into the solution, thereby affecting removal efficiency. Ultrasonic stirring in the cathode chamber significantly enhanced Sb removal from high-concentration solutions (5 mg/L), while magnetic stirring was more suitable for lower-concentration solutions. Orthogonal experiments revealed that due to the competitive relationship between hydrogen generation and SbH3 generation, as well as the gas-blocking effect, current intensity and electrode area both had a significant impact on Sb removal. Under appropriate current intensity and electrode area conditions (0.5 A, 20 cm²), a high removal rate of 78.5 ± 4.6% can be achieved. Consequently, employing a Nafion membrane coupled with ultrasonic agitation under optimized conditions (30°C, 25 mA/cm²) effectively accelerates antimony removal kinetics and enhances elimination efficiency. However, the substantial reduction in current efficiency and elevated energy consumption induced by competitive hydrogen evolution represent critical challenges requiring urgent resolution. This treatment approach provides a technical reference‌ for shifting from mere contaminant removal to resource recovery. The integration of removal and recovery processes holds substantial potential‌ for implementing circular economy models in mining and metallurgical industries.